The effects of bilingualism on stuttering during late childhood. Issue 1 (9th September 2008) - Howell, P; Davis, S; Williams, R
Abstract : Objectives: To examine stuttering by children speaking an alternative language exclusively (LE) or with English (BIL) and to study onset of stuttering, school performance and recovery rate relative to monolingual speakers who stutter (MONO). Design: Clinical referral sample with supplementary data obtained from speech recordings and interviews. Setting: South-East England, 1999–2007. Participants: Children aged 8–12 plus who stuttered (monolingual and bilingual) and fluent bilingual controls (FB). Main outcome measures: Participants' stuttering history, SATS scores, measures of recovery or persistence of stuttering. Results: 69 (21.8%) of 317 children were bilingual. Of 38 children who used a language other than English at home, 36 (94.7%) stuttered in both languages. Fewer LE (15/38, 39.5%) than BIL (23/38, 60.5%) children stuttered at first referral to clinic, but more children in the fluent control sample were LE (28/38, 73.7%) than BIL (10/38, 26.3%). The association between stuttering and bilingual group (LE/BIL) was significant by χ 2 test; BIL speakers have more chance of stuttering than LE speakers. Age at stuttering onset and male/female ratio for LE, BIL and MONO speakers were similar (4 years 9 months, 4 years 10 months and 4 years 3 months, and 4.1:1, 4.75:1 and 4.43:1, respectively). Educational achievement was not affected by bilingualism relative to the MONO and FB groups. The recovery rate for the LE and MONO controls together (55%) was significantly higher by χ 2 test than for the BIL group (25%). Conclusions: BIL children had an increased risk of stuttering and a lower chance of recovery from stuttering than LE and MONO speakers.